The young riders of Mongolia - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Horse riding is a very important tradition in Mongolia. Each year the people here have a special race to celebrate this tradition. However, this race is a little unusual. What type of race is i and why is it unusual?
Title from title screen
Video and audio on DVD
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography